Audit Kinerja sebagai Instrumen Peningkatan Akuntabilitas Publik di Sektor Pemerintahan - Faizal, Dyan; Prasetya Nugrahanti, Trinandari (Ikatan Da'i Indonesia, 2025)
Performance audit is one of the supervisory instruments that plays a strategic role in promoting improved public accountability in the government sector. Along with the increasing public demand for transparency, effectiveness, and efficiency in governance, performance audit has become increasingly relevant as an evaluation tool for the implementation of public programs and policies. Unlike financial audits, which focus on the fairness of financial statements, performance audits emphasize the assessment of effectiveness, efficiency, and economy (value for money) in the management of public resources. This article aims to comprehensively examine the role of performance audits as an instrument for enhancing public accountability in the government sector through a literature review approach. The research method employed is a library study by analyzing national and international scientific journals, reference books, laws and regulations, as well as relevant reports from audit institutions. The results of the review indicate that performance audits significantly contribute to improving transparency, accountability, decision-making quality, and continuous improvement in public sector governance. In addition, performance audits function as a means of evaluating public policies and strengthening public trust in the government. This article is expected to provide a conceptual contribution to the development of performance audit practices and the enhancement of public accountability in the government sector.